Antibiotics and shared decision-making in primary care. - Butler, C; Kinnersley, P; Prout, H; Rollnick, S; Edwards, A; Elwyn, G (2001)
Antibiotics are often prescribed to patients with respiratory tract infections who are unlikely to benefit. Models of physician-patient interaction may help understanding of this problem and inform the design of communication skills interventions to enhance appropriate prescribing. The 'paternalistic model' of the consultation remains common in the setting of acute respiratory tract infections. However, the four assumptions that could support this model are not valid for most of these patients, because: best treatment is controversial; management is inconsistent; physicians are not in the best position to evaluate trade-offs between management options without understanding patients' perspectives; and many pressures (apart from patients' agendas) intrude into the consultation. One alternative is the 'informed model' of consulting, but this does not take society's interests into account. The 'shared decision-making model', however, provides a framework for addressing both clinicians' and patients' agendas, and could guide the development and evaluation of specific consultation strategies to promote more appropriate use of antibiotics in primary care.